The digital hood: Social media use among youth in disadvantaged neighborhoods. (June 2017) - Stevens, Robin; Gilliard-Matthews, Stacia; Dunaev, Jamie; Woods, Marcus K; Brawner, Bridgette M
This study examines the role of social media in the lives of youth living in disadvantaged neighborhoods. Feminist Standpoint Theory, which privileges the voices of marginalized communities in understanding social phenomena, suggests that youth at the margins have specific knowledge that helps us understand social media more broadly. We conducted semi-structured interviews with 30 females and 30 males aged 13–24 years about their social worlds and neighborhoods, both online and offline. The findings reveal a dynamic and somewhat concerning interplay between the geographic neighborhood and the digital neighborhood, whereby negative social interactions in the geographic neighborhood are reproduced and amplified on social media.